Effect of abdominal aortic calcification on long‐term outcomes after the first liver resection in very old patients with hepatocellular carcinoma - Yosuke Namba; Masahiro Ohira; Yuki Imaoka; Michinori Hamaoka; Masakazu Hashimoto; Takashi Onoe; Daisuke Takei; Koichi Oishi; Megumi Yamaguchi; Tomoyuki Abe; Takeshi Tadokoro; Sotaro Fukuhara; et al. (Annals of Gastroenterological Surgery)
Abstract Aim We previously reported that abdominal aortic calcification is associated with poor overall and recurrence‐free survival after hepatectomy for hepatocellular carcinoma (HCC). However, the effect of abdominal aortic calcification on cancer‐specific prognosis in very old patients with several comorbidities remains unknown. This multicenter study aimed to evaluate the impact of abdominal aortic calcification on the cumulative recurrence rate and recurrence‐free survival in patients with HCC aged >80 years. Methods We retrospectively analyzed the data of 128 patients (aged ≥80 years) who underwent liver resection for hepatocellular carcinoma at seven hospitals belonging to Hiroshima Surgical Study Group of Clinical Oncology between January 2014 and December 2018. Patients were divided into two groups: high and low abdominal aortic calcification groups. The primary endpoints were cumulative recurrence rate and recurrence‐free survival. Results Kaplan–Meier survival curve analysis demonstrated that the cumulative recurrence rate in the high abdominal aortic calcification group was significantly higher than that in the low abdominal aortic calcification group, and the high abdominal aortic calcification group had a significantly lower recurrence‐free survival rate. In the multivariate analysis, high abdominal aortic calcification (p = 0.03), high des‐gamma‐carboxyprothrombin score (p = 0.04), and multiple tumors (p < 0.01) were independent predictive factors for recurrent HCC, and high abdominal aortic calcification (p = 0.01) and high des‐gamma‐carboxyprothrombin (p = 0.01) were independent predictive factors for poor cancer‐specific survival. Conclusions Our results indicate that the abdominal aortic calcification score is associated with cumulative recurrence rate and recurrence‐free survival in very old patients with HCC.